Implementasi Kebijakan Pemberdayaan Masyarakat Berbasis Local Wisdom Dalam Kegiatan Pariwisata Di Desa Lumban Suhi-Suhi Toruan Kabupaten Samosir - Harles Berman Lumbantobing; Tunggul Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
In public policy about tourism it is mentioned tourism is not only building infrastructure but protect human right, cultural diversity, local wisdom and community local empowerment. Therefore, the implementation of tourism must have an impact on the lives of local communities and its implementation must involve the community to participate in implementing these policies. For this reason, it is necessary to implement local wisdom-based community empowerment in tourism activities so that the community structure that participates in tourism can be independent and prosperous.The purpose of this research was to determine the implementation of community empowerment based local wisdom policies in tourism activities at Lumban Suhi-Suhi Toruan village, Samosir Regency. The method used in this study is descriptive qualitative using the theory of M.S. Grindle stated that implementation can be seen from several indicators, namely related interests, type of benefits, degree of change to be achieved, location of decision making, program implementers, resources used, power, interests and actors involved, character of institutions and regimes those in power, and the level of compliance and response from the implementer.The implementation of community empowerment based on local wisdom policies in Lumban Suhi-Suhi Toruan village like Martonun Sadari, Hita Do Hutaraja and ulos weaving training have not been optimally. The obstacle factor because the lack of resources owned by the village and regional governments, along with the weaving ulos group, causing the benefits of the policies obtained to be less felt by the empowered community.